Does schooling moderate the relationship between morphological awareness and spelling? - Alves Santos , Dalva Silva; Fernandes Martins , Leonardo; Brilhante Guimarães, Silvia; Deacon, S. Héléne; Peruzzi Elia da Mota, Marcia Maria (Revista de Investigación en Logopedia, 2025)
Children's awareness of morphemes improves over the elementary school years, but its role in determining literacy skills, particularly those in spelling, is still an open question. To answer this question, 100 children in Grades 2 and 3 completed morphological and phonemic awareness tasks, spelling, as well as a control measure of general ability. The results showed that the relationship between morphological awareness and spelling is moderated by grade. The model with the control and explanatory variables explained 30.0% of the variability in spelling scores, and adding the interaction term showed a statistically significant contribution, indicating that grades moderates the contribution of morphological awareness, particularly that of inflectional morphology to spelling. Morphological awareness is a stronger predictor of spelling in Grade 3 than in Grade 2, even after controls were carried out. We discuss the implications of these findings for theory and practice.
Keywords: Spelling; Morphology; Morphological Awareness; Metalinguistic Awareness